Biyahera - Tan, Joven
Gina, Lilia, Alice and Lorraine are four waitresses who work in a canteen along a highway. The owner of the canteen is Lucas, a temperamental boss who treats them like prisoners. Although all the girls aspire for a better life, none of them have the courage to go against Lucas. Working alongside the highway where the canteen is located is Mildred, a prostitute. Like the four waitresses, she has her own journey.